2018
DOI: 10.1002/jpen.1424
|View full text |Cite
|
Sign up to set email alerts
|

Association of Anthropometric and Nutrition Status Indicators with Hand Grip Strength and Gait Speed in Older Adults

Abstract: In older adults, lower values of height and calf circumference, as well as higher waist circumference, were associated with both low GS and HGS. Lower values of mid-arm muscle circumference were also associated with low values of both functional parameters only in men. The risk for undernutrition/undernutrition was more strongly associated with low GS than with low HGS in both women and men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 49 publications
1
22
0
2
Order By: Relevance
“…Keeping in line with our observations, GS has shown significant associations with low height [ 52 ], higher BMI [ 53 ] and low bone mineral density (BMD) [ 54 ]. The associations seen between GS and height and BMI are understandable.…”
Section: Discussionsupporting
confidence: 70%
“…Keeping in line with our observations, GS has shown significant associations with low height [ 52 ], higher BMI [ 53 ] and low bone mineral density (BMD) [ 54 ]. The associations seen between GS and height and BMI are understandable.…”
Section: Discussionsupporting
confidence: 70%
“…First, some factors related to muscle strength, such as the nutritional status of the participants, were not included in this study. These factors may be included in future following-up studies with home-visit interventions 32 . Second, for the HGS test, most of the older adults took the measurements in a standing position, with the exception of some older people who took the procedure in a sitting position to prevent falls.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with previous research that HGS and gait speed were reported as good predictors of functional disability, morbidity, and mortality in older adults. 58 According to the literature, a gait speed 0.8 m/s might be used to identify older adults with mobility impairment because this cutoff predicts disability and reduced overall survival. 59 The present study results revealed that worse nutritional and functional statuses were directly associated with a higher risk of mortality in community-dwelling older adults with mild-to-moderate AD.…”
Section: Discussionmentioning
confidence: 99%